ANALYSIS OF STUDENT INTEREST TO BECOME ISLAMIC ENTERPRENEURSHIP (LONGITUDINAL RESEARCH) - Hardiyanto Wibowo; Fatmah Bagis; Mega Aprillia Pratamasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Theory of Planned Behavior (TPB) is a theory that has been widely applied in various fields of behavioral research. TPB states that the combination of attitudes towards behavior, subjective norms, and perceived behavioral control leads to the formation of behavioral intentions and then shapes behavior (behavior). There may be some research related to student interests that has been carried out. This research is very necessary because the tendency of current students is to have a desire to find work and the interest in becoming an entrepreneur is very minimal. This research was conducted for 8 months. The study population was students in semester 1 (one) of the Faculty of Economics and Business, University of Muhammdiyah Purwokerto (FEB UMP). Primary data collection techniques by observation and discussion, direct observation in the field using a questionnaire that is distributed. The data analysis method used is Partial Least Square (PLS). The results of the study show that there is an increase in student interest in becoming Islamic Entrepreneurs after attending Islamic entrepreneurship lectures. And the results of the analysis also show that the role of providing entrepreneurial material significantly influences students' interest in becoming an Islamic entrepreneur. Hopefully the results of this research will provide support for the entrepreneurship clinical work program at the University and can be used as material for consideration for the next agenda. Keywords: Islamic entrepreneurship, interest.